Usage of Chlorella and diverse microalgae for CO2 capture - towards a bioenergy revolution - Ashour, Mohamed; Mansour, Abdallah Tageldein; Alkhamis, Yousef A.; Elshobary, Mostafa (Frontiers in Bioengineering and Biotechnology, 2024)
To address climate change threats to ecosystems and the global economy, sustainable solutions for reducing atmospheric carbon dioxide (CO2) levels are crucial. Existing CO2 capture projects face challenges like high costs and environmental risks. This review explores leveraging microalgae, specifically the Chlorella genus, for CO2 capture and conversion into valuable bioenergy products like biohydrogen. The introduction section provides an overview of carbon pathways in microalgal cells and their role in CO2 capture for biomass production. It discusses current carbon credit industries and projects, highlighting the Chlorella genus’s carbon concentration mechanism (CCM) model for efficient CO2 sequestration. Factors influencing microalgal CO2 sequestration are examined, including pretreatment, pH, temperature, irradiation, nutrients, dissolved oxygen, and sources and concentrations of CO2. The review explores microalgae as a feedstock for various bioenergy applications like biodiesel, biooil, bioethanol, biogas and biohydrogen production. Strategies for optimizing biohydrogen yield from Chlorella are highlighted. Outlining the possibilities of further optimizations the review concludes by suggesting that microalgae and Chlorella-based CO2 capture is promising and offers contributions to achieve global climate goals.